VITAMIN D INSUFFICIENCY IN CHILDREN OF TENDER YEARS IN RUSSIA: THE RESULTS OF A MULTI-CENTRE COHORT STUDY RODNICHOK (2013-2014) - I. N. Zakharova; S. V. Mal'tsev; Т. E. Borovik; G. V. Yatsyk; S. I. Malyavskaya; I. V. Vakhlova; Т. А. Shumatova; Ye. B. Romantsova; F. P. Romanyuk; L. Ya. Klimov; N. I. Pirozhkova; S. М. Kolesnikova; et al. ("Paediatrician" Publishers LLC, 2014)
Background: Vitamin D insufficiency is a widespread phenomenon, having an adverse effect on human health. This problem is also actual in Russia, which most part of the territory is located above the 42nd latitude and is at risk for vitamin D insufficiency. Objective: Our aim was to evaluate the vitamin D sufficiency of the child population of a junior age group and the adequacy of a drug treatment/prevention of vitamin D insufficiency in various regions of the Russian Federation. Methods: Children of the first 3 years of life, who received in-patient treatment in medical institutions of Russia, were examined. When they were involved in the study, they took a blood test to determine a plasma 25(OH)D concentration. The study period: November, 2013 - October, 2014. Results: 1,230 children aged from 1 month to 3 years were examined. Vitamin D insufficiency (25(OH)D concentration in the blood plasma 21-29 ng/ml) is found in 300 (24.4%), deficiency (25(OH)D ≤ 20 ng/ml) - in 513 (41.7%) children. The prevalence of vitamin D insufficiency and deficiency did not depend on a geographical location and level of insolation of regions, where the surveyed lived. Conclusion: In the studied selection more than 2/3 of children of a junior age group have a vitamin D insufficiency or deficiency. In this regard, it is expedient to revise the current guidelines taking into account modern approaches to the prevention and treatment of a vitamin D insufficiency, to make the appropriate changes and to implement them in a clinical practice.